LUDWIG VAN BEETHOVEN ARTYSTA W KRĘGU FILOZOFII, LITERATURY, RELIGII, TECHNIKI I SPRAW POLITYCZNO-SPOŁECZNYCH - Dudek, Marek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Ludwig van Beethoven was a man always looking for his own path. As an artist, he was able to overcome stereotypes and introduce his listeners to feelings, thoughts and states of mind which went beyond their awareness. His works removed boundaries of musical literality, not infrequently becoming a record of experiences of ordinary people. The accompanying enthusiasm and aesthetic innovativeness reflected the composer’s interests which oscillated around numerous fields of science, ranging from philosophy, literature, religion, technology to political and social issues. From the beginning, he was a self-taught composer, fascinated by changeability of the world. His intention was to draw upon it as much as possible and to express as much on the pages of his scores. He suffered but he knew how to win. Though he was lonely, he touched millions. He amazed to the last, never losing the curiosity of a child.